Futuristic Non-antibiotic Therapies to Combat Antibiotic Resistance: A Review - Kumar, Manoj; Sarma, Devojit Kumar; Shubham, Swasti; Kumawat, Manoj; Verma, Vinod; Nina, Praveen Balabaskaran; JP, Devraj; Kumar, Santosh; Singh, Birbal; Tiwari, Rajnarayan R. (Frontiers in Microbiology, 2021)
The looming problem of resistance to antibiotics in microorganisms is a global health concern. The drug-resistant microorganisms originating from anthropogenic sources and commercial livestock farming have posed serious environmental and health challenges. Antibiotic-resistant genes constituting the environmental “resistome” get transferred to human and veterinary pathogens. Hence, deciphering the origin, mechanism and extreme of transfer of these genetic factors into pathogens is extremely important to develop not only the therapeutic interventions to curtail the infections, but also the strategies to avert the menace of microbial drug-resistance. Clinicians, researchers and policymakers should jointly come up to develop the strategies to prevent superfluous exposure of pathogens to antibiotics in non-clinical settings. This article highlights the present scenario of increasing antimicrobial-resistance in pathogenic bacteria and the clinical importance of unconventional or non-antibiotic therapies to thwart the infectious pathogenic microorganisms.